KAJIAN BEBERAPA SIFAT KIMIA TANAH PODSOLIK MERAH KUNING PADA LAHAN PERKEBUNAN KELAPA SAWIT BERBEDA UMUR DI SEI DAUN, KABUPATEN LABUHANBATU SELATAN, SUMATERA UTARA - Sihaloho, Elisa Putri Br; Afany, Miseri Roeslan; Peniwiratri , Lelanti (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2024)
Red-yellow podzolic soils are generally acidic and have poor chemical properties, so tolerant plants such as oil palm plants are needed. This research was to determine the effect of differences in the age of oil palms on the chemical properties of the Sei Daun plantation soil. The research was conducted in December 2022 using the method of purposive sampling according to plant age. Samples were taken from 5 lands with oil palm ages 8 years, 14 years, 16 years, and 25 years, as well as land without plants, 5 points were determined from each land, and each point was separated into 3 depths, namely 0-20 cm, 20-50 cm, and 50-70 cm, the 5 points were composited according to depth, producing 3 samples per field. The results of the analysis of soil chemical properties show that increasing the age of oil palm causes soil pH, thereby reducing available P, total N, exchangeable K, and CEC of soil, but increasing soil organic C, also increasing Fe-NH4OAC, Mn-NH4OAC, exchangeable Al but still in low value. Increasing the age of oil palms can lower the soil pH, thereby reducing the availability of nutrients. Fertilizer doses can be adjusted according to the age of the plant because the older it is, the more nutrients the plant absorbs.